Offense of Spreading Infectious Disease and Methods of Proof Through Forensic Science (International Seminar on Syariah and Law (INSLA), 2020)
Since 1988, a specific Act has been enacted concerning the prevention and control of infectious diseases. This Act is known as the Prevention and Control of Infectious Diseases Act 1988. The preamble to this Act states that it was enacted to amend and consolidate laws relating to the prevention and control of infectious diseases and to provide for other matters relating thereto. In this Act, there are several types of actions that if committed can be convicted as an offense under this Act, among them include acting in a manner that can spread infectious diseases. This study discusses matters related to offense causing the spread of infectious diseases from the view of civil and Syariah law. It also covers scientific methods to prove such offense. This qualitative study has collected relevant data through primary and secondary documents and subsequently analysed it using the document analysis method. The result of this study found that the act of exposing others to the risk of infection is an offense and it is forbidden in Islam. Several scientific methods can be used in convicting this offense; among them are medical reports, travel records, physical examinations, CCTV footage, and biological examinations. This study suggests that the aspect of proof for such cases should be emphasized because such studies have not yet been conducted by previous researchers.